Waralaba Sebagai Kerjasama Dalam Kegiatan Bisnis Menurut Hukum Ekonomi Islam - Azizatur Rahmah (CERED Indonesia Institute, 2022)
Franchising is a business concept carried out by means of marketing or distributing goods or services to consumers as a form of expansion (business expansion), by offering or franchising the business to a prospective second party, namely the franchisee (franchisee), and the party franchising the business is called franchisee (franchisor). The franchise business opens up many business opportunities for the community and can improve the welfare of the community because it provides comfort, cleanliness and competitive prices as well as quality products. In the franchise business, openness, honesty and prudence are applied. But on the other hand, to protect the Indonesian people, who are predominantly Muslim, it is necessary to examine the clarity of the franchise business from the perspective of Islamic Economic Law. Islamic Economic Law provides opportunities for the development of Muslim thinking in dealing with all problems in this era of globalization, including determining the legality of franchise businesses based on Islamic Economic Law. The purpose of this study is to determine the franchise in Islamic economic law. The research method used is normative juridical, the data collection method is by means of library research